SIMULASI DENGAN PENDEKATAN METODE GREEN LEAN MANUFACTURING GUNA MENGEVALUASI PEMBOROSAN WAKTU PADA PT. ANS DENGAN SISTEM DINAMIS - Salsabila, Naswa; Ahmad; Andres (Jurnal Mitra Teknik Industri, 2025)
This manufacturing company operates in the automotive industry with a Make to Order (MTO) production system, producing motorcycle engine components. Observations revealed production inefficiencies due to waste in the form of waiting time and excessive motion, leading to increased operational time and costs. This study aims to identify sources of waste, analyze root causes, and propose improvements using the Green Lean Manufacturing approach, which emphasizes both production efficiency and environmental considerations. The methods applied include Value Stream Mapping (VSM), Fishbone Diagram, 5 Why’s analysis, and system dynamics simulation. Based on the Current VSM analysis, the lead time was 268.21 minutes with a Process Cycle Efficiency (PCE) of 77.32%. Proposed improvements include relocating materials closer to machines, preparing tools before production, and adding workplace facilities. The Future VSM showed a lead time reduction of 17.92 minutes and a PCE increase of 1.17%. From the three simulated scenarios, ANOVA test results indicated that Scenario 3 was the most effective in reducing motion waste, while Scenario 2 best reduced waiting time. Both scenarios demonstrated the effectiveness of continuous lean implementation over a five-year period.